Symmetrical composite electrode and preparation method and application thereof
The composite electrodes doped with lanthanum ferrate perovskite and cerium oxide were prepared by the "one-pot method", and nanometal particles were precipitated in situ, solving the problems of excessive oxygen partial pressure and uneven distribution of the two phases of the composite electrode in SOEC, achieving higher catalytic activity and lower electrical energy requirements.
Patent Information
- Application Number
- CN202510048192.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-13
AI Technical Summary
In traditional solid oxide electrolytic cell (SOEC), exposure to the anode in the air causes excessive oxygen partial pressure, hindering oxygen ion transfer, and the composite cathode has problems of uneven distribution of the two phases and scarce active sites.
The "one-pot method" is used to self-assemble the doped cubic phase lanthanum-based perovskite and doped cubic fluorite-type cerium oxide composite electrode, and the nanometal particles are precipitated by in-situ reduction to form a symmetric composite electrode.
The catalytic activity of oxygen reduction reaction and carbon dioxide reduction reaction is improved, the electrical energy demand is reduced, the thermal expansion coefficient of the electrode is reduced, and the problems of carbon accumulation and agglomeration during the deposition of nanometal catalysts are solved.
Smart Images

Figure CN119913555A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrode technology, and in particular to a symmetrical composite electrode and a preparation method and application thereof. Background Art
[0002] Solid oxide electrolyzer (SOEC) has the ability to convert CO2 into CO or other high-value chemicals. However, in traditional SOEC, the anode is directly exposed to the air, which makes the excessive oxygen partial pressure on the anode side an obstacle to the transfer of oxygen ions. To overcome this obstacle, a large amount of electricity must be input, so electricity becomes the main cost of this technology. From the perspective of economic effect, reducing the demand for electricity is extremely critical for the application of SOEC. In terms of electrolysis performance, the electrode material of SOEC is usually made of a physical mixture of two materials with good carbon dioxide reduction reaction (CO2RR) catalytic activity and good ionic conductivity and electronic conductivity, and then made into a composite cathode. However, this composite cathode has shortcomings such as uneven distribution of the two phases and scarce active sites. Summary of the invention
[0003] The purpose of the present invention is to provide a symmetrical composite electrode and a preparation method and application thereof in view of the above-mentioned deficiencies in the prior art.
[0004] The present invention discloses a symmetrical composite electrode, wherein the catalyst of the symmetrical composite electrode is a doped cubic lanthanum ferrite-based perovskite oxide and a doped fluorite-based cerium oxide prepared by a "one-pot method" self-assembly, and doped metal nanoparticles are precipitated in situ; the chemical formula of the doped cubic lanthanum ferrite-based perovskite is (La 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 1.0-x M x ]O 3-δ , chemical formula of doped fluorite-type cerium oxide Gd 0.075 Ce 0.925-y M y O 2-δ , M is any one of the transition metal elements Ru, Rh, Co, Ni, Cu, x=0-0.2, y=0-0.05, δ=0-0.15, and the doped metal nanoparticles are M single substance.
[0005] Furthermore, the doped cubic phase lanthanum ferrite-based perovskite (La 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 1.0-x M x ]O 3-δ and doped fluorite-type cerium oxide Gd 0.075Ce 0.925-y M y O 2-δ The specific operation of the composite precursor is:
[0006] S11: Dissolve citric acid in an amount equal to the amount of metal ions in water and stir to completely dissolve, then dissolve La source, Sr source, Fe source, Nb source, Gd source, Ce source and M source in a stoichiometric ratio, where M is any one of Ru, Rh, Co, Ni and Cu. After all the above metal salts are dissolved, add concentrated nitric acid to adjust the pH value to 1, then add EDTA, the molar ratio of EDTA to metal ions is 2:1, adjust the pH value to 6-7 with ammonia water, heat and stir until spontaneous combustion occurs, and collect the black powder after spontaneous combustion;
[0007] S12: The black powder obtained in step S11 is subjected to heat preservation, decarbonization and high-temperature sintering to obtain a doped cubic phase lanthanum ferrite-based perovskite (La 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 1.0-x M x ]O 3-δ and doped fluorite-type cerium oxide Gd 0.075 Ce 0.925- y M y O 2-δ Composite precursor powder.
[0008] Further, in step S12, the cubic phase lanthanum ferrite-based perovskite (La 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 1.0- x M x ]O 3-δ and doped fluorite-type cerium oxide Gd 0.075 Ce 0.925-y M y O 2-δ The mass ratio is 6-7:3-4.
[0009] Furthermore, in step S12, the black powder is kept at 550-650°C for 2 hours to remove carbon, and then the obtained powder is sintered at 1000-1200°C for 5 hours.
[0010] A method for preparing the above-mentioned symmetrical composite electrode comprises the following steps:
[0011] S1: Preparation of doped cubic lanthanum ferrite-based perovskite (La) by one-pot self-assembly 0.5 Sr 0.5 )[(Fe0.9 Nb 0.1 ) 1.0-x M x ]O 3-δ and doped fluorite-type cerium oxide Gd 0.075 Ce 0.925-y M y O 2-δ Composite precursors;
[0012] S2: The precursor and the additive are mixed and ground to prepare a slurry, which is screen-printed on both sides of the solid electrolyte layer and sintered to prepare a battery;
[0013] S3: The battery is in-situ reduced at a working temperature and in a reducing atmosphere, and metal nanoparticles are precipitated from the electrode precursor to obtain the symmetrical composite electrode.
[0014] Furthermore, in step S2, the auxiliary agent is terpineol containing 7.5-10 wt.% of ethyl cellulose.
[0015] Furthermore, the mass ratio of the precursor to the auxiliary agent is 1:1-2.
[0016] Furthermore, in step S3, the working temperature is 700°C to 800°C, the reducing atmosphere is pure hydrogen, and the in-situ reduction time is 30 to 60 minutes.
[0017] An application of the symmetrical composite electrode as described above is used as cathode and anode of a solid oxide electrolysis cell to electrolyze carbon dioxide.
[0018] Furthermore, a methanol atmosphere is maintained at the anode of the solid oxide electrolysis cell, CO2 is continuously input at the cathode, and CO2 is electrolyzed while methanol is oxidized at the anode.
[0019] The present invention uses the "one-pot method" and the in-situ dissolution method to prepare a special composite electrode for the first time. The composite electrode contains doped lanthanum ferrite perovskite, doped cerium oxide catalyst, and its surface is coated with nano metal M particles. Compared with the composite electrode prepared by the traditional physical mixing method, the perovskite-electrolyte interface synthesized by the "one-pot method" shows many advantages, such as better two-phase connection effect, lower thermal expansion coefficient, and more active sites, which enables it to obtain more excellent oxygen reduction reaction (OER) and carbon dioxide reduction reaction (CO2RR) catalytic activity. When the battery is at an operating temperature of 700-800°C, a reducing gas is introduced, and the nano metal particles M are precipitated in situ. The metal particle heterostructure is tightly combined with the composite electrode material, has good dispersibility, and the embedded structure ensures good electrode stability, which can effectively solve the problems of carbon deposition and agglomeration that traditional nano metal catalysts are prone to in the deposition process.
[0020] The preparation method of the composite electrode of the present invention is synthesized under simple conditions, and the method is simple, easy to implement, low in cost, and has good repeatability. In addition, the electrode has excellent electrocatalytic activity for both methanol oxidation and carbon dioxide reduction.
[0021] The present invention aims to reduce the use cost of SOEC and improve its reaction efficiency, and proposes a method of introducing CH3OH as an auxiliary gas at the anode to reduce energy consumption. On the anode side, CH3OH will undergo an oxidation reaction to generate two valuable gases, CO and H2, which are ideal gases for the Fischer-Tropsch synthesis reaction. At the same time, the anode can transfer electrons to the cathode through the solid electrolyte, participate in the reduction reaction on the cathode side, and then reduce the reaction overpotential, effectively improving the reaction rate and efficiency. Moreover, the reduction of oxygen partial pressure at the anode is conducive to overcoming the transfer barrier of oxygen ions, and the partial oxidation reaction at the anode can also compensate for the heat required for co-electrolysis, achieving the effect of reducing power consumption and reducing costs. The experimental results show that the anode methanol auxiliary significantly reduces the applied voltage, polarization resistance and total power consumption of SOEC electrolysis, providing a new approach and application prospect for CO2 conversion and energy utilization.
[0022] In addition, methanol has the advantages of low price, easy transportation and storage, not easy to decompose, and an industrial chain with considerable scale effect due to its special production method and physical and chemical properties. The high heat demand of SOEC can be met with the help of waste heat resources, such as industrial waste heat and low-cost electricity during the "peak shaving and valley filling" period. In summary, the present invention provides new ideas and methods for reducing the energy consumption of SOEC, and also creates new application paths for the utilization of industrial waste heat and carbon dioxide conversion. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1a This is a thermodynamic analysis diagram of conventional CO2 electrolysis performed by SOEC in Example 1;
[0024] Figure 1b This is a thermodynamic analysis diagram of CO2 electrolysis by CH3OH-assisted SOEC in Example 1;
[0025] Figure 2a The XRD pattern of the Ru-LSFN / Ru-GDC composite electrode precursor prepared by the one-pot method in Example 1;
[0026] Figure 2b XRD pattern of Ru@Ru-LSFN / Ru@Ru-GDC prepared by in-situ exsolution method;
[0027] Figure 3a This is a SEM image of the Ru-LSFN / Ru-GDC precursor prepared in Example 1;
[0028] Figure 3bThis is the SEM image of Ru@Ru-LSFN / Ru@Ru-GDC prepared in Example 1;
[0029] Figure 4a -d, is the XPS comparison chart of Ru 3p, Ce 3d, Fe 2p, O 1s of Ru-LSFN / Ru-GDC precursor and Ru@Ru-LSFN / Ru@Ru-GDC prepared according to the technical scheme of this embodiment;
[0030] Figure 5a The current-voltage diagram of the SOEC of the first embodiment performing conventional CO2 electrolysis and CH3OH-assisted CO2 electrolysis;
[0031] Figure 5b The impedance diagram of the SOEC of the first embodiment under the open circuit voltage for conventional CO2 electrolysis and CH3OH-assisted CO2 electrolysis;
[0032] Figure 6 This is a comparison chart of the power consumption of the SOEC of the first embodiment for conventional CO2 electrolysis and CH3OH-assisted CO2 electrolysis;
[0033] Figure 7 Schematic diagram of the process of CO2 electrolysis using CH3OH-assisted SOEC. DETAILED DESCRIPTION
[0034] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0035] Embodiment 1:
[0036] (La 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 0.8 Ru 0.2 ]O 3-δ (hereinafter referred to as Ru-LSFN) and Gd 0.075 Ce 0.875 Ru 0.05 O 2-δ The composite electrode with a mass ratio of 6:4 (hereinafter referred to as Ru-GDC) was abbreviated as (Ru-LSFN / Ru-GDC). The same mole of citric acid as the metal ions of the previous two chemical formulas was weighed and added into 100 mL of deionized water and stirred until completely dissolved. Then, La(NO3)3·6H2O, Sr(NO3)2, Fe(NO3)3·9H2O, C 10 H5B 20·xH2O, RuCl3, Gd(NO3)3·6H2O, (NH4)2Ce(NO3)6 are dissolved in sequence, and then concentrated nitric acid is added to adjust the pH value to 1, and then EDTA is added, and the molar number of EDTA: total cations is 2:1. Use ammonia water to adjust the pH to 6-7. Heat the solution and stir it continuously until the solution forms a gel and undergoes a spontaneous combustion process. Take the powder after spontaneous combustion and move it into a muffle furnace and keep it at 600℃ for two hours. After cooling down, the obtained powder is fully ground and heated to 1100℃ and kept at this temperature for 5h to obtain a composite electrode precursor.
[0037] Take the composite electrode precursor prepared previously, add pinene alcohol containing 7.5-10wt.% ethyl cellulose, control the mass ratio of the precursor to pinene alcohol to be 1:1.5, mix and grind for several hours to obtain the electrode slurry. Use the screen printing method to evenly coat the electrode slurry on both sides of the dense LSGM electrolyte with a thickness of 250μm, and then dry the electrode. After drying, place it in an air atmosphere and sinter it at a temperature of 1050℃ for 2h to complete the preparation of the single cell.
[0038] The single cell was packaged and tested. The cathode and anode were first purged with N2 at 800°C to remove the air and then pure H was introduced for in-situ reduction for 30 min. The precursor powder was reduced to Ru@(La 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 0.8 Ru 0.2 ]O 3-δ / Ru@Gd 0.075 Ce 0.875 Ru 0.05 O 2-δ (hereinafter referred to as Ru@Ru-LSFN / Ru@Ru-GDC). After N2 was introduced to purge the excess H2, methanol was introduced into the anode and CO2 was introduced into the cathode for SOEC electrolysis test.
[0039] Table 1 Comparison of thermodynamic and operating parameters of different electrolyzers
[0040]
[0041] See Appendix 1. Among various anode-assisted electrolysis of carbon dioxide, anode CH3OH(g)-assisted electrolysis of CO2 shows significant advantages. Compared with other common reactions such as electrolysis involving C and CH4(g)-assisted electrolysis, the total energy required for anode CH3OH(g)-assisted electrolysis of CO2 is relatively low. From the energy data, the total energy required for CH3OH(g)-assisted electrolysis of carbon dioxide is only 139.17KJ mol -1 , and the total energy required for C electrolysis is 169.88KJ mol -1The total energy required for the electrolysis of CH4(g) is as high as 293.45KJ mol -1 In addition, the power required for CH3OH(g)-assisted electrolysis of CO2 is -161.53KJ mol -1 , which is at the lowest level among several reactions, which means it is more economical in terms of electricity consumption. On the whole, the anode CH3OH(g)-assisted SOEC shows outstanding superiority in energy demand, with higher energy utilization efficiency and lower operating costs. The high heat demand of CH3OH(g)-assisted SOEC can be obtained through the utilization of waste heat resources. The heat can come from industrial waste heat, concentrated solar panels or waste heat electricity, etc. Taking ethylene production as an example, the cracking furnace is the core equipment for ethylene production, and its outlet temperature can reach 800℃-900℃, and the cracking gas contains a large amount of waste heat.
[0042] Attached Figure 1a This is a thermodynamic analysis diagram of traditional CO2 electrolysis. Figure 1b This is a thermodynamic analysis diagram of CO2 electrolysis assisted by anode CH3OH in SOEC. At 800℃ and the anode is in CH3OH atmosphere, the total reaction Gibbs free energy increases from 189.21KJ mol -1 Down to -161.93KJ mol -1 , indicating that in theory, the energy requirement of CH3OH-assisted SOEC is much lower than that of conventional SOEC. The thermal effect of the partial oxidation reaction of CH3OH at the anode can provide the heat required for SOEC operation, reduce the anode oxygen partial pressure, and accelerate the kinetics of cathode CO2RR.
[0043] See attached Figure 2a , is the XRD pattern of the Ru-LSFN / Ru-GDC composite electrode precursor prepared by the one-pot method according to the technical solution of this embodiment. The results show that the precursor material Ru-LSFN exhibits a cubic perovskite phase, and Ru-GDC exhibits a cubic fluorite phase structure.
[0044] See attached Figure 2b , is the XRD pattern of Ru@Ru-LSFN / Ru@Ru-GDC prepared by in-situ exsolution method according to the technical scheme of this embodiment. The peak of metal Ru appears after in-situ reduction, and the reduced material includes cubic perovskite-type doped lanthanum ferrite perovskite, cubic fluorite-type doped cerium oxide and single metal M precipitated in-situ on the surface of the two materials.
[0045] See attached Figure 3a , is a SEM image of the Ru-LSFN / Ru-GDC precursor prepared according to the technical solution of this embodiment. The image shows that the particles are agglomerated and have a cloud-like structure. The two different powders, Ru-LSFN and Ru-GDC, are tightly combined and have a good combination effect. See the attached Figure 3b, is a SEM image of Ru@Ru-LSFN / Ru@Ru-GDC prepared according to the technical solution of this embodiment. The results show that the surface of the material is evenly covered with metal Ru nanoparticles embedded in the substrate.
[0046] See attached Figure 4a -d, is the XPS comparison of Ru 3p, Ce 3d, Fe 2p, and O 1s of the Ru-LSFN / Ru-GDC precursor and Ru@Ru-LSFN / Ru@Ru-GDC prepared according to the technical scheme of this embodiment; From the Ru 3p spectrum, it can be observed that Ru 0 The signal indicates that part of Ru was reduced to Ru metal precipitation. The XPS comparison of Ce 3d and Fe 2p shows that Ru@Ru-LSFN / Ru@Ru-GDC has a lower ion valence than Ru-LSFN / Ru-GDC. According to the principle of electrical neutrality, the reduction of metal ion valence usually corresponds to the generation of oxygen vacancies to maintain electrical neutrality. The XPS comparison of O 1s shows that the lattice oxygen content of Ru@Ru-LSFN / Ru@Ru-GDC decreases after reduction, and the surface oxygen vacancies increase, which is conducive to the formation and diffusion of oxygen vacancies.
[0047] See attached Figure 5a , which is the IV curve of the conventional CO2 electrolysis of SOEC and the CH3OH-assisted SOEC assembled according to Example 1. The results show that the CH3OH-assisted anode significantly reduces the applied voltage. For example, at 0.8A cm -2 At the electrolysis current density of , the voltage required for simple CO2 electrolysis by SOEC is 1.5V, while when assisted by anode CH3OH, the applied voltage is only 0.33V, which is reduced by 1.17V.
[0048] See attached Figure 5b , is the impedance diagram under open circuit voltage for conventional CO2 electrolysis and CH3OH-assisted CO2 electrolysis according to the SOEC of this embodiment 1. After CH3OH was introduced into the anode, the polarization resistance at 800°C was significantly reduced.
[0049] See attached Figure 6 , is a comparison of the power consumption of conventional CO2 electrolysis and CH3OH-assisted CO2 electrolysis by SOEC according to the first embodiment. It can be seen that the power consumption required for CH3OH-assisted SOEC to generate one cubic meter of CO is significantly reduced. For example, at 800°C, with a voltage of 1.5V, the power consumed to generate one cubic meter of CO is 3.68kWh m -3 , while the voltage applied by CH3OH-assisted electrolysis SOEC at the same current density is only 0.33V, and the power consumed is only 0.40kWh m -3, which is only 10.87% of the traditional SOEC. The huge energy-saving effect has greatly reduced the cost, and CH3OH-assisted SOEC has shown a wider application prospect in the fields of energy conversion and chemical industry.
[0050] Figure 7 Schematic diagram of the process of CO2 electrolysis using CH3OH-assisted SOEC.
[0051] Embodiment 2:
[0052] (La 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 0.8 R 0.2 ]O 3-δ (hereinafter referred to as Rh-LSFN) and Gd 0.075 Ce 0.875 R 0.05 O 2-δ The mass ratio of the composite electrode (hereinafter referred to as Rh-GDC) is 6:4, and the citric acid with the same mole as the metal ions of the previous two chemical formulas is weighed and added into 100 mL of deionized water and stirred until completely dissolved. Then, La(NO3)3·6H2O, Sr(NO3)2, Fe(NO3)3·9H2O, C 10 H5B 20 ·xH2O, Rh(NO3)3·nH2O, Gd(NO3)3·6H2O, (NH4)2Ce(NO3)6 are dissolved in sequence, and then concentrated nitric acid is added to adjust the pH value to 1, and then EDTA is added, and the molar number of EDTA: total cations is 2:1. Use ammonia water to adjust the pH to 6-7. Heat and stir continuously until the solution forms a gel and spontaneous combustion occurs. Take the powder after spontaneous combustion and move it into a muffle furnace and keep it at 600℃ for two hours. After cooling down, grind the obtained powder thoroughly and heat it to 1100℃ and keep it at this temperature for 5h to obtain the composite electrode precursor.
[0053] Take the composite electrode precursor prepared previously, add pinene alcohol containing 7.5-10wt.% ethyl cellulose, control the mass ratio of the precursor to pinene alcohol to be 1:1.5, mix and grind for several hours to obtain the electrode slurry. Use the screen printing method to evenly coat the electrode slurry on both sides of the dense LSGM electrolyte with a thickness of 250μm, and then dry the electrode. After drying, place it in an air atmosphere and sinter it at a temperature of 1050℃ for 2h to complete the preparation of the single cell.
[0054] The single cell was packaged and tested. The cathode and anode were first purged with N2 to remove the air at 800°C, and then pure H was introduced for in-situ reduction for 60 min. The precursor powder was reduced to Rh@(La 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 0.8 R 0.2 ]O 3-δ / Rh@Gd 0.075 Ce 0.875 R 0.05 O 2-δ (hereinafter referred to as Rh@Rh-LSFN / Ru@Rh-GDC). After N2 was introduced to purge the excess H2, methanol was introduced into the anode and CO2 was introduced into the cathode for SOEC electrolysis test. The performance results of conventional CO2 electrolysis and CH3OH-assisted CO2 electrolysis of SOEC according to Example 2 show that at 0.8A cm -2 At the electrolysis current density of , the voltage required for SOEC to electrolyze CO2 alone is 1.5V, while when assisted by anode CH3OH, the applied voltage is only 0.54V, which is reduced by 0.96V.
[0055] Embodiment three:
[0056] (La 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 0.8 Co 0.2 ]O 3-δ (hereinafter referred to as Co-LSFN) and Gd 0.075 Ce 0.875 Co 0.05 O 2-δ The mass ratio of the composite electrode (hereinafter referred to as Co-GDC) is 6:4, and the citric acid with the same mole of metal ions as the previous two chemical formulas is weighed and added into 100 mL of deionized water and stirred until completely dissolved. Then, La(NO3)3·6H2O, Sr(NO3)2, Fe(NO3)3·9H2O, C 10 H5B 20·xH2O, Co(NO3)3·6H2O, Gd(NO3)3·6H2O, (NH4)2Ce(NO3)6 are dissolved in sequence, and then concentrated nitric acid is added to adjust the pH value to 1, and then EDTA is added, and the molar number of EDTA: total cations is 2:1. Use ammonia water to adjust the pH to 6-7. Heat and stir continuously until the solution forms a gel and spontaneous combustion occurs. Take the powder after spontaneous combustion and move it into a muffle furnace and keep it at 600℃ for two hours. After cooling down, grind the obtained powder thoroughly and heat it to 1100℃ and keep it at this temperature for 5h to obtain the composite electrode precursor.
[0057] Take the composite electrode precursor prepared previously, add pinene alcohol containing 7.5-10wt.% ethyl cellulose, control the mass ratio of the precursor to pinene alcohol to be 1:1.5, mix and grind for several hours to obtain the electrode slurry. Use the screen printing method to evenly coat the electrode slurry on both sides of the dense LSGM electrolyte with a thickness of 250μm, and then dry the electrode. After drying, place it in an air atmosphere and sinter it at a temperature of 1050℃ for 2h to complete the preparation of the single cell.
[0058] The single cell was packaged and tested. The cathode and anode were first introduced into N2 to purge the air at 800°C, and then pure H was introduced into the cathode and anode for in-situ reduction for 60 min. The precursor powder was reduced to Co@(La 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 0.8 Co 0.2 ]O 3-δ / Co@Gd 0.075 Ce 0.875 Co 0.05 O 2-δ (hereinafter referred to as Co@Co-LSFN / Ru@Co-GDC). After N2 was introduced to purge the excess H2, methanol was introduced into the anode and CO2 was introduced into the cathode for SOEC electrolysis test. The test results showed that at 0.8A cm -2 At the electrolysis current density of , the voltage required for SOEC to electrolyze CO2 alone is 1.5V, while when assisted by anode CH3OH, the applied voltage is only 0.61V, which is reduced by 0.89V.
[0059] Embodiment 4:
[0060] (La 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 0.8 Ni 0.2 ]O 3-δ (hereinafter referred to as Ni-LSFN) and Gd0.075 Ce 0.875 Ni 0.05 O 2-δ The composite electrode with a mass ratio of 7:3 (hereinafter referred to as Ni-GDC) was abbreviated as (Ni-LSFN / Ni-GDC). The same mole of citric acid as the metal ions of the previous two chemical formulas was weighed and added into 100 mL of deionized water and stirred until completely dissolved. Then La(NO3)3·6H2O, Sr(NO3)2, Fe(NO3)3·9H2O, C 10 H5B 20 ·xH2O, Ni(NO3)2·6H2O, Gd(NO3)3·6H2O, (NH4)2Ce(NO3)6 are dissolved in sequence, and then concentrated nitric acid is added to adjust the pH value to 1, and then EDTA is added, and the molar number of EDTA: total cations is 2:1. Use ammonia water to adjust the pH to 6-7. Heat and stir continuously until the solution forms a gel and spontaneous combustion occurs. Take the powder after spontaneous combustion and move it into a muffle furnace and keep it at 600℃ for two hours. After cooling down, grind the obtained powder thoroughly and heat it to 1100℃ and keep it at this temperature for 5h to obtain the composite electrode precursor.
[0061] Take the composite electrode precursor prepared previously, add pinene alcohol containing 7.5-10wt.% ethyl cellulose, control the mass ratio of the precursor to pinene alcohol to be 1:1.5, mix and grind for several hours to obtain the electrode slurry. Use the screen printing method to evenly coat the electrode slurry on both sides of the dense LSGM electrolyte with a thickness of 250μm, and then dry the electrode. After drying, place it in an air atmosphere and sinter it at a temperature of 1050℃ for 2h to complete the preparation of the single cell.
[0062] The single cell was packaged and tested. The cathode and anode were first introduced into N2 to purge the air at 800°C, and then introduced into pure H for in-situ reduction for 60 min. The precursor powder was reduced to Ni@(La 0.5 Sr 0.5 )1[(Fe 0.9 Nb 0.1 ) 0.8 Ni 0.2 ]O 3-δ / Ni@Gd 0.075 Ce 0.875 Ni 0.05 O 2-δ (hereinafter referred to as Ni@Ni-LSFN / Ru@Ni-GDC). After N2 was introduced to purge the excess H2, methanol was introduced to the anode and CO2 was introduced to the cathode for SOEC electrolysis test. The test results of the single cell performance showed that at 0.8Acm -2At the electrolysis current density of , the voltage required for SOEC to electrolyze CO2 alone is 1.5V, while when assisted by anode CH3OH, the applied voltage is only 0.64V, which is reduced by 0.86V.
[0063] Embodiment five:
[0064] (La 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 0.8 Cu 0.2 ]O 3-δ (hereinafter referred to as Cu-LSFN) and Gd 0.075 Ce 0.875 Ru 0.05 O 2-δ The composite electrode (Cu-LSFN / Cu-GDC) with a mass ratio of 6:4 was abbreviated as (Cu-LSFN / Cu-GDC). The same mole of citric acid as the metal ions of the previous two chemical formulas was weighed and added into 100 mL of deionized water and stirred until completely dissolved. Then La(NO3)3·6H2O, Sr(NO3)2, Fe(NO3)3·9H2O, and C were weighed according to the stoichiometric ratio. 10 H5B 20 ·xH2O, Cu(NO3)2·3H2O, Gd(NO3)3·6H2O, (NH4)2Ce(NO3)6 are dissolved in sequence, and then concentrated nitric acid is added to adjust the pH value to 1, and then EDTA is added, and the molar number of EDTA: total cations is 2:1. Use ammonia water to adjust the pH to 6-7. Heat and stir continuously until the solution forms a gel and spontaneous combustion occurs. Take the powder after spontaneous combustion and move it into a muffle furnace and keep it at 600℃ for two hours. After cooling down, grind the obtained powder thoroughly and heat it to 1100℃ and keep it at this temperature for 5h to obtain the composite electrode precursor.
[0065] Take the composite electrode precursor prepared previously, add pinene alcohol containing 7.5-10wt.% ethyl cellulose, control the mass ratio of the precursor to pinene alcohol to be 1:1.5, mix and grind for several hours to obtain the electrode slurry. Use the screen printing method to evenly coat the electrode slurry on both sides of the dense LSGM electrolyte with a thickness of 250μm, and then dry the electrode. After drying, place it in an air atmosphere and sinter it at a temperature of 1050℃ for 2h to complete the preparation of the single cell.
[0066] The single cell was packaged and tested. The cathode and anode were first introduced into N2 to purge the air at 800°C, and then introduced into pure H for in-situ reduction for 30 min. The precursor powder was reduced to Cu@(La 0.5 Sr 0.5 )[(Fe 0.9Nb 0.1 ) 0.8 Cu 0.2 ]O 3-δ / Cu@Gd 0.075 Ce 0.875 Cu 0.05 O 2-δ (hereinafter referred to as Cu@Cu-LSFN / Ru@Cu-GDC). After N2 was introduced to purge the excess H2, methanol was introduced to the anode and CO2 was introduced to the cathode for SOEC electrolysis test. The test results of the single cell performance showed that at 0.8Acm -2 At the electrolysis current density of , the voltage required for SOEC to electrolyze CO2 alone is 1.5V, while when assisted by anode CH3OH, the applied voltage is only 0.53V, which is reduced by 0.97V.
[0067] For matters not mentioned above, the prior art applies.
[0068] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A symmetrical composite electrode, characterized in that: The catalyst of the symmetrical composite electrode is a one-pot self-assembled cubic lanthanum ferrite-based perovskite oxide and a fluorite-based cerium oxide, and in-situ precipitation of doped metal nanoparticles; the chemical formula of the cubic lanthanum ferrite-based perovskite is (La 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 1.0-x M x ]O 3-δ , chemical formula of doped fluorite-type cerium oxide Gd 0.075 Ce 0.925-y M y O 2-δ , M is any one of the transition metal elements Ru, Rh, Co, Ni, Cu, x=0-0.2, y=0-0.05, δ=0-0.15, and the doped metal nanoparticles are M single substance.
2. A symmetrical composite electrode as claimed in claim 1, characterized in that: Preparation of doped cubic lanthanum ferrite-based perovskite (La) by one-pot self-assembly 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 1.0-x M x ]O 3-δ and doped fluorite-type cerium oxide Gd 0.075 Ce 0.925-y M y O 2-δ The specific operation of the composite precursor is: S11: Dissolve citric acid in an amount equal to the amount of metal ions in water and stir to completely dissolve, then dissolve La source, Sr source, Fe source, Nb source, Gd source, Ce source and M source in a stoichiometric ratio, where M is any one of Ru, Rh, Co, Ni and Cu. After all the above metal salts are dissolved, add concentrated nitric acid to adjust the pH value to 1, then add EDTA, the molar ratio of EDTA to metal ions is 2:1, adjust the pH value to 6-7 with ammonia water, heat and stir until spontaneous combustion occurs, and collect the black powder after spontaneous combustion; S12: The black powder obtained in step S11 is subjected to heat preservation, decarbonization and high-temperature sintering to obtain a doped cubic phase lanthanum ferrite-based perovskite (La 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 1.0-x M x ]O 3-δ and doped fluorite-type cerium oxide Gd 0.075 Ce 0.925-y M y O 2-δ Composite precursor powder.
3. A symmetrical composite electrode as claimed in claim 2, characterized in that: In step S12, the cubic phase lanthanum ferrite-based perovskite (La 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 1.0-x M x ]O 3-δ and doped fluorite-type cerium oxide Gd 0.075 Ce 0.925-y M y O 2-δ The mass ratio is 6-7:3-4.
4. A symmetrical composite electrode as claimed in claim 2, characterized in that: In step S12, the black powder is kept at 550-650°C for 2 hours to remove carbon, and then the obtained powder is sintered at 1000-1200°C for 5 hours.
5. A method for preparing a symmetrical composite electrode according to any one of claims 1 to 4, characterized in that: The steps include: S1: Preparation of doped cubic lanthanum ferrite-based perovskite (La) by one-pot self-assembly 0.5 Sr 0.5 )[(Fe 0.9 Nb 0.1 ) 1.0- x M x ]O 3-δ and doped fluorite-type cerium oxide Gd 0.075 Ce 0.925-y M y O 2-δ Composite precursors; S2: The precursor and the additive are mixed and ground to prepare a slurry, which is screen-printed on both sides of the solid electrolyte layer and sintered to prepare a battery; S3: The battery is in-situ reduced at a working temperature and in a reducing atmosphere, and metal nanoparticles are precipitated from the electrode precursor, thereby obtaining the symmetrical composite electrode.
6. The preparation method according to claim 5, characterized in that: In step S2, the auxiliary agent is terpineol containing 7.5-10 wt.% of ethyl cellulose.
7. The preparation method according to claim 5, characterized in that: The mass ratio of the precursor to the auxiliary agent is 1:1-2.
8. The preparation method according to claim 5, characterized in that: In step S3, the working temperature is 700°C to 800°C, the reducing atmosphere is pure hydrogen, and the in-situ reduction time is 30 to 60 minutes.
9. An application of the symmetrical composite electrode according to any one of claims 1 to 4, characterized in that: Used as cathode and anode in solid oxide electrolysis cells to electrolyze carbon dioxide.
10. A use according to claim 9, characterized in that: A methanol atmosphere is maintained at the anode of the solid oxide electrolysis cell, and CO2 is continuously input at the cathode. While methanol is oxidized at the anode, CO2 is electrolyzed.
Citation Information
Patent Citations
Catalyst composition
CN101146615A
Anode material containing alkali metal or alkaline-earth metal element of solid oxide fuel cell and preparation method and application thereof
CN104078687A
CO2-resistant high-stability dual-phase oxygen-permeable membrane material and preparation method thereof
CN104803683A
Method for preparing composite negative electrode on cerium-based electrolyte isolation layer through low-temperature sintering
CN106876755A
Symbiotic fuel cell anode as well as preparation method and application thereof
CN113451588A